Arturo Nannizzi (1877-1961): “a singular scientist” in the history of mycology - Davide Orsini; Simone Di Piazza; Mirca Zotti; Mariano Martini (Italian Journal of Mycology)
Arturo Nannizzi was a singular scientist from Siena, who, thanks to a deep commitment and an extraordinary experience linked to uncommon intellectual abilities, was able to make up for the lack of a formal curriculum of studies. Thanks to the availability of the teacher Gino Pollacci, who called him as a collaborator, Nannizzi participated in a scientific project of great importance: the preparation and publication of a work that would become a milestone in the field of applied mycology “I miceti patogeni dell’uomo e degli animali”. Nannizzi also made a fundamental contribution to the taxonomy of dermatophytes, having been the first to demonstrate the complete development of the sexual state of a dermatophyte. Often opposed during his activity for the fact that he did not have a degree, his work was re-evaluated only after his death.